An Analysis of Bank Syariah Indonesia digital services and features - Abidin, Zaenal; Octira, Mila (AL-FALAH : Journal of Islamic Economics, 2024)
Aligned with technological advancements and evolving customer preferences for cutting-edge banking solutions, Bank Syariah Indonesia (BSI) has introduced the BSI Mobile Application, aiming to deliver efficient banking services in adherence to Sharia financial principles. This study is prompted by the quest for a comprehensive understanding of the digital services offered by BSI, specifically focusing on identifying distinctive features, evaluating integration levels, and assessing their impact on the operational efficiency of the bank. Employing a qualitative approach through the library research method, the research draws data from diverse sources, including literature, scientific journals, books, official documents, and pertinent information accessible through library repositories and digital platforms.Utilizing a literature study as the primary data collection technique and applying the Miles and Huberman data analysis method, this research ensures the validity and reliability of findings by relying on credible sources such as scientific journals and official documents from Bank Syariah Indonesia. The outcomes of this research successfully unveil and elaborate on the array of digital services provided by BSI, highlighting distinctive features that set it apart from conventional mobile banking applications. The analysis of BSI Mobile features offers profound insights into services that embody a holistic approach, demonstrating efficiency and compliance with Sharia financial principles.This research serves as a foundational knowledge source for future inquiries. The anticipation is that a more profound comprehension of digital service types, specific features, and their effects on BSI's operational efficiency will serve as a guide for developing more efficacious strategies in the future. The envisaged positive contribution aims to optimize digital services at BSI, enhance the overall customer experience, and elevate the operational efficiency of the bank.